2022
DOI: 10.1039/d2dt00560c
|View full text |Cite
|
Sign up to set email alerts
|

Metal–organic frameworks in pursuit of size: the development of macroscopic single crystals

Abstract: Metal-organic frameworks are versatile structures with many different applications, from the industry to the clinic. Despite multiple synthesis approaches are possible to coordinate metals and organic ligands, some common strategies...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Synthesizing a large single crystal is intriguing not only in its critical role to correlate the intrinsic property with the material structure 13,14 but also for the utilities (e.g., optical 15 and electrical 16 devices) where crystal size matters. 17 Some reports also revealed that large MOF crystals show superior 18 or even inverted 19 performance compared to the smaller counterparts. However, the fast nucleation kinetics in most MOFs usually results in small crystals because the precursors are rapidly consumed to generate new nuclei while a few are left for growth, 20 posing a great difficulty in synthesizing large MOF single crystals.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesizing a large single crystal is intriguing not only in its critical role to correlate the intrinsic property with the material structure 13,14 but also for the utilities (e.g., optical 15 and electrical 16 devices) where crystal size matters. 17 Some reports also revealed that large MOF crystals show superior 18 or even inverted 19 performance compared to the smaller counterparts. However, the fast nucleation kinetics in most MOFs usually results in small crystals because the precursors are rapidly consumed to generate new nuclei while a few are left for growth, 20 posing a great difficulty in synthesizing large MOF single crystals.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs), piled up by simple molecular bricks following the idea of reticular chemistry, are cutting-edge porous crystalline materials with almost infinite possibilities in terms of both architecture and functionality. Typically, most MOFs are obtained in powder form or as nanocrystals, which, however, limits some applications where only large bulk single crystals are qualified. Synthesizing a large single crystal is intriguing not only in its critical role to correlate the intrinsic property with the material structure , but also for the utilities (e.g., optical and electrical devices) where crystal size matters . Some reports also revealed that large MOF crystals show superior or even inverted performance compared to the smaller counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Growing MOF single crystals to millimeter dimensions is a significant challenge. [27][28][29][30] Unlike more commonly used nonlinear optical materials such as potassium dihydrogen phosphate KH 2 PO 4 (KDP), of which the growth mechanism and kinetics are well known, [31] the general factors that control the self-assembly and crystallization mechanisms of MOF structures are largely unknown. [32][33][34] Recent progress in this direction was reported in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, complexes with large-size crystals are not only conducive to the accurate determination and analysis of structures but also provide a potential possibility for use in single crystal devices in practical applications. 25,26 Therefore, large single crystals are considered to be a convenient platform to study the intrinsic properties of a complex and to assess the "structure-property" interconnection. Despite the increasing interest in large-size complex single crystals, the strategies for obtaining such materials have not been fully studied, resulting in a relatively slow development in this field, because the influence of the external environment and internal factors on the crystal formation process is extremely complex (such as the reaction temperature, time, pH, cooling rate, reactant concentration, ratio, etc.).…”
Section: Introductionmentioning
confidence: 99%